The impact of prenatal education based on the Roy adaptation model on gestational hypertension, adaptation to pregnancy and pregnancy outcomes - Amanak, Keziban; Sevil, Umran; Karacam, Zekiye (Journal of the Pakistan Medical Association, 2019)
To analyse the impact of prenatal education on gestational hypertension, adaptation to pregnancy and on maternal and neonatal outcomes. The quasi-experimental case-control study was conducted at Aydin Maternity and Children's Hospital, Aydin, Turkey, from October 2013 to July 2015, and comprised women with gestational hypertension. The sample was randomised into education and control groups with the former receiving informative education and the latter receiving due medical care alone. Roy Adaptation Model was used to determine the impact of prenatal education. SPSS 20 was used for data analysis. Of the 132 subjects, 68(51.5%) were in the education group and 64(48.5%) in the control group. Postintervention, 11(16.2%) women in the education group and 37(57.8%)in the control group developed severe preeclampsia. Subsequently, 44(64.7%) in the education group had no preeclampsia. The corresponding number in the control group was 15(23.4%). Education based on Roy Adaptation Model proved to be effective among pregnant women in keeping hypertension under control.